THE EFFECTIVENESS OF MIND MAPS IN IMPROVING THE UNDERSTANDING OF STRESS MANAGEMENT IN GRADE 5 STUDENTS OF TASDIKIAH THAILAND - Muhammad Haikal Abror; Putri Ria Angelina; Noneng Siti Rosidah (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This research is motivated by the low understanding of students in the learning process caused by the lecture method which tends to make students passive, boring, sleepy and less involved in learning. This condition not only impacts learning outcomes, but also affects the psychological aspects of students, in the form of stress originating from academic, family and social pressures. Therefore, an interactive, effective and easy-to-understand method is needed to support stress management with classical services. This study aims to determine the effectiveness of the mind map method in improving understanding of stress management in grade 5 students of Tasdikiah Thailand. The method used is a quantitative experiment with a Quasi Experiment Nonequivalent Control Group Design. This study provided a pretest and posttest to the experimental class and the control class to see the differences in the two groups. The population in this study were all students of grades 5.1 and 5.3, totaling 64 people, where grade 5.1 was designated as the experimental class given treatment and grade 5.3 as the control class. Sampling was used with incidental sampling techniques, this sample was based on students who happened to be there at the time of the study. The results of this study found that; 1) the pretest results of the experimental class averaged 9.53 and the control class averaged 5.83; 2) the posttest results of the experimental class averaged 11.89 and the control class 6.92; 3) this hypothesis test was carried out through a non-parametric test, namely the Man-Whitney U test, obtained a sig value (2-tailed) of 0.000 <0.05, so there is a significant difference between the experimental and control classes. So Ha is accepted and Ho is rejected, which shows that this study is effective in improving understanding of stress management.